Long-term climate change in the D-region. Issue 1 (December 2017) - Clilverd, Mark; Duthie, Roger; Rodger, Craig; Hardman, Rachael; Yearby, Keith
Abstract Controversy exists over the potential effects of long-term increases in greenhouse gas concentrations on the ionospheric D-region at 60–90 km altitudes. Techniques involvingin-situ rocket measurements, remote optical observations, and radio wave reflection experiments have produced conflicting results. This study reports a novel technique that analyses long-distance subionospheric very low frequency radiowave observations of the NAA 24.0 kHz transmitter, Cutler, Maine, made from Halley Station, Antarctica, over the period 1971–2016. The analysis is insensitive to any changes in the output power of the transmitter, compensates for the use of different data logging equipment, and can confirm the accuracy of the timing systems operated over the 45 year long record. A ~10% reduction in the scale size of the transmitter nighttime interference fringe pattern has been determined, taking into account the quasi-11 year solar cycle. Subionospheric radiowave propagation modeling suggests that the contraction of the interference fringe pattern about the mid-latitude NAA transmitter is due to a 3 km reduction in the effective height of the nighttime ionospheric D-region over the last 45 years. This is consistent with the effect of enhanced infra-red cooling by increasing greenhouse gases.